Artikel Model Pembelajaran Cooperative Learning - Kezya Meylani Fernanda Putri; Lidiya Rima Ranti; Glen Hosea Fernando Ringkat (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Education is one of the most important things for the quality of human life. To carry out education correctly, it is necessary to prepare various things such as learning models, methods, and techniques to help the learning process. This time we are trying to present information about one of the cooperative learning models and three examples of its application in the classroom, namely group investigation and round robin. The research of this journal aims to present information related to the cooperative learning model. The method used in writing this journal is the literature method. The results of this study are in the form of material presentations regarding the meaning of the cooperative learning model, the syntax of the cooperative learning model, and examples.